«Russian statism» and «Russian nihilism» in russia’s political process of the late XIX - early XX centuries - N. A. Omelchenko (Управление)
The article is devoted to the study of traditional foundations of Russian political culture and their influence on formation of national characteristics of political relations, political transit and political process as a whole. The author gives a description of the basic fundamental features of Russian political culture that for a long period of time determined the main vector of social development in Russia, as well as approaches to, and points of view on the nature and reasons for their formation existing in Russian scholarship. The article gives an overall assessment of the factors behind the specifics of state and political development of Russia. Among these are: «anticapitalist» and «antiproprietory» mentality of Russian people, state paternalism, sacralization of power. But the most important factor is the leading role of the state in regulating political and social life of the society (statism). This fundamental peculiarity of the political process in Russia accounts for a specific national «profile» of public policy which delimits the possibility of development in the country of civil society with its attributes and characteristics. The main task of the author is the study of origins, nature and character of the relationship between Russian statism and political radicalism that for a long time were two basic features of the Russian political tradition. The article substantiates the idea that Russian statism, as a traditional basis of Russian political culture, and Russian nihilism were historically and objectively interconnected and interdependent. They complemented each other and formed the Russian authorities’ world outlook accounting for a nihilistic attitude to complex manifestations of real life, a bias for simplified generalizations and schemes, dogmatism in building their ideals characteristic for Russian political and intellectual elite. The author maintains that this, among other things, was the reason for the breakdown of Russia in 1917 that led to the collapse of historical statism.